IMPLEMENTATION OF INTERNET-BASED EMERGENCY MEDICAL SERVICE: A SOLUTION TO IMPROVE RESPONSE TIME IN OUT-OF-HOSPITAL CARDIAC ARREST AND ITS POTENTIAL APPLICATION IN INDONESIA - Ismail Fahmi; Elly Nurachmah (Belitung Raya Foundation, Indonesia, 2018)
Out-of-Hospital Cardiac Arrest (OHCA) is a condition when heart stops beating in out of the hospital. The majority of OHCA leads to death because of the delay response. Emergency Medical Service (EMS) system is needed to take care of the patients carefully. The development of Internet-based EMS is one of the best solutions, which is not only to improve the response time, but also to help patients to get the ambulance immediately. The aim of this paper is to understand how the Internet-based EMS can be used and how it will affect the patients with OHCA. Our findings indicated that the Internet-based EMS with mobile web service is critically needed for immediate response of cardiac arrest and accident situation in pre-hospital condition. However, the Internet-based EMS development needs to involve inter-sectoral agencies, such as fire fighter, police, and National Search and Rescue (SAR) Agent. This article has been updated. A separate erratum can be seen at https://doi.org/10.33546/bnj.1147